Cholinergic Hypofunction in Presbycusis-Related Tinnitus With Cognitive Function Impairment: Emerging Hypotheses - Ruan, Qingwei; Yu, Zhuowei; Zhang, Weibin; Ruan, Jian; Liu, Chunhui; Zhang, Ruxin (Frontiers in Aging Neuroscience, 2018)
Presbycusis (age-related hearing loss) is a potential risk factor for tinnitus and cognitive deterioration, which result in poor life quality. Presbycusis-related tinnitus with cognitive impairment is a common phenotype in the elderly population. In these subjects, the central auditory system shows similar pathophysiological alterations as those observed in Alzheimer’s disease (AD), including cholinergic hypofunction, epileptiform-like network synchronization, chronic inflammation, and reduced GABAergic inhibition and neural plasticity. Observations from experimental rodent models indicate that recovery of cholinergic function can improve memory and other cognitive functions via acetylcholine-mediated GABAergic inhibition enhancement, nicotinic acetylcholine receptor (nAChR)-mediated anti-inflammation, glial activation inhibition, and neurovascular protection. The loss of cholinergic innervation of various brain structures may provide a common link between tinnitus seen in presbycusis-related tinnitus and age-related cognitive impairment. We hypothesize a key component of the condition is the withdrawal of cholinergic input to a subtype of GABAergic inhibitory interneuron, neuropeptide Y (NPY) neurogliaform cells. Cholinergic denervation might not only cause the degeneration of NPY neurogliaform cells, but may also result in decreased AChR activation in GABAergic inhibitory interneurons. This, in turn, would lead to reduced GABA release and inhibitory regulation of neural networks. Reduced nAChR-mediated anti-inflammation due to the loss of nicotinic innervation might lead to the transformation of glial cells and release of inflammatory mediators, lowering the buffering of extracellular potassium and glutamate metabolism. Further research will provide evidence for the recovery of cholinergic function with the use of cholinergic input enhancement alone or in combination with other rehabilitative interventions to reestablish inhibitory regulation mechanisms of involved neural networks for presbycusis-related tinnitus with cognitive impairment.